2021
DOI: 10.1136/rmdopen-2020-001558
|View full text |Cite
|
Sign up to set email alerts
|

The arthritis connection to inflammatory bowel disease (IBD): why has it taken so long to understand it?

Abstract: Inflammatory bowel disease (IBD) associated arthritis is a subgroup of spondyloarthritis (SpA) that has suffered from lack of recognition in rheumatology clinical and research circles for over 100 years. Although clinically distinguishable from rheumatoid arthritis and ankylosing spondylitis, it took advances in detection systems in the middle of the last century (rheumatoid factor, HLA-B27) to convincingly make the final separations. We now know that significant numbers of patients with SpA have associated cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 89 publications
0
21
1
Order By: Relevance
“…According to the current literature, microbiome dysregulation and its driven T helper 17 cell expansion and immune cell migration to the joint in a proper genetic background may play a role. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…According to the current literature, microbiome dysregulation and its driven T helper 17 cell expansion and immune cell migration to the joint in a proper genetic background may play a role. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…As many as 10% of individuals with axial SpA (axSpA) are diagnosed with co-morbid IBD, and up to 50% of individuals with axSpA will present with sub-clinical bowel inflammation that is detectable by biopsy but is not sufficient for a diagnosis of IBD (8). This observation has led to the generation for the gutjoint hypothesis in axSpA (9)(10)(11), which proposes that inflammatory disease begins and is driven by host-microbe interactions in the gut and then spreads to distal sites, ultimately presenting as inflammatory back pain. Multiple studies have reported increases in circulating and synovial populations of Th17 polarized T cells, ILC3s, mucosa-associated invariant T cells (MAITs), and TCRgd+ T cells (12)(13)(14)(15), all of which are generally thought to be generated and/or activated through microbiome-mediated mechanisms at the mucosa and are capable of production of TNF and IL-17 (16), the primary mediators of disease in axSpA (3).…”
Section: Introductionmentioning
confidence: 99%
“…Establishing the diagnosis of IID-associated SpA at an early stage is a very difficult task: the clinical manifestations are minor, but the radiological manifestations are reliable and are usually detected on average 7.1 years after the onset of symptoms [13]. A group of Italian researchers reported that the diagnosis of SpA in patients with IID is after around 5.2 years from the onset of dorsal pain.…”
Section: Introductionmentioning
confidence: 99%